Law and Leadership Style: How Could the Leader Promote the Effective Law Enforcement? (Case of Correctional Institution Class IIA Pekalongan) - Firdausyah, Egitya; Ashraff, Muh (Indonesian Journal of Advocacy and Legal Services, 2021)
According to PP Number 27 of 1983, State Detention Centers, hereinafter referred to as detention centers, are places for suspects and defendants to be detained during the process of investigation, prosecution and examination at court proceedings. In carrying out the duties and authority of the detention center, it is certainly controlled by a leader. In this case the leader in question is the head of the detention center. The head of the detention center in running the leadership wheel must have the skills to lead subordinates. There are several styles or models of leadership, one of which is the situational leadership style, where the leader is more concerned with the situation, when to be pushy and when to moderate. Leadership is certainly associated with performance. Performance is a result of both the quality and quantity performed by officers in carrying out their work. From this understanding, researchers are interested in conducting research related to the influence of situational leadership style on the performance of correctional officers using the correlation method where the independent variable is the influence of the situational leadership style, and the dependent variable is the performance of correctional officers in class IIA Pekalongan Detention Center. Based on the statistical data analysis that the researchers conducted, it can be concluded that the situational leadership style has an effect on the performance of correctional officers in the Class IIA Pekalongan Detention Center.